Why Integrity and not Coherence? - Gasparyan, Gayane (Armenian Folia Anglistika, 2011)
The present article considers such text categories as integrity and coherence. The latter is expressed by two different terms in English – cohesion and coherence. There are different approaches towards these two terms, which, however, lead to nearly the same conclusion. The former (integrity) is a means of combining intertextual units while the latter (coherence) is the category ensuring the unity of the text and establishing a link between both intertextual and extra-textual situations and environments. Integrity in its turn, is viewed as a means of integrating text elements into a whole and helping to create an intertextual and extratextual context that is closely related to the category of coherence.